COAL LIQUEFACTION IN INDONESIA: CURRENT STATUS AND FUTURE PROGRAMME - NINING S. NINGRUM; BUKIN DAULAY (Puslitbang tekMIRA, 2007)
The Presidential Decree No. 5/2006 and Presidential Instruction No. 2/2006 about Supply and Exploi- tation of Liquefied Coal as Other Fuel has instructed the interrelated department, including the Ministry of Energy and Mineral Resources, to bring about the development of coal liquefaction plant in Indone- sia, and make use of its product - in the form of oil fuel. To implement the instruction, the Coordinating Ministry for Economic Affairs issued Decision Letter, No. KEP-11/M.EKON/02/2006 about Coordina- tor of Team Action Programmed Supply and Use of Alternative Energy and KEP-01/D.III.M.EKON/02/ 2006 about Technical Coordinator Action Programme Supply and Use of Alternative Energy. Some activities that have been done by the coal liquefaction team in 2006 were the socialization of coal liquefaction to introduce the coal liquefaction technology to the investors. It is expected that the investors will be interested in investing their financial capital in the coal liquefaction.